Pengembangan Museum Virtual Reality Sejarah Pemerintah Darurat Republik Indonesia (PDRI) untuk Menggugah Empati Sejarah Siswa - Anjely, Monica; Aisiah, Aisiah (Jurnal Kronologi, 2025)
This research is motivated by the importance of innovation in interactive history learning media to increase students' historical understanding and empathy for national historical events. However, limitations of interactive and interesting media often become an obstacle in conveying teaching material, especially about PDRI, to students. In general, this research aims to develop Museum media Virtual Reality (MVR) PDRI uses Artsteps.com And Canva for studying history in high school. The research method applies Research and Development (R&D) with a 4D development model (Define, Design, Develop, Disseminate). The results of the research show that the MVR PDRI material feasibility validation score is 3.8 and the average PDRI MVR media feasibility validation score is 3.36. The average PDRI MVR practicality test result by teachers was 3.53 (very practical) and the average practicality test result score by students was 2.94. It can be concluded that the development of PDRI MVR learning media is in the appropriate category for increasing students' understanding and empathy and is practical in its use as supporting media in history learning.